Advantages of Using Expert Systems to Project Dairy Cattle Farms: Case Study of Turkey, Menemen - Ilkay ALKAN (Journal of Animal and Plant Sciences, 2024)
This study aimed to research the advantages of using information technologies in the design of architectural projects of dairy cattle farms. In this context, 3 dairy cattle farms in Izmir – Menemen region, whose projects were designed with traditional methods and received rural development support, were picked as samples and they were examined using an expert system called “Architectural Designing of Dairy Farms” (ADDF). The existing infrastructure in the sample farms and the herd management strategies allowed by this infrastructure were compared with the herd management applications recommended by ADDF for each farm and the infrastructure facilities required by such strategies. It has been determined that there are design errors in the barns that will adversely affect animal welfare. In this context, it has been emphasized which mistakes can be avoided if expert systems are used and recommended to use the expert systems in the design of architectural projects of dairy cattle farms in order to use the investments effectively and to increase the efficiency in animal production.
Keywords: Dairy cattle housing; Animal welfare; Expert system